Using surfacing welding technology to manufacture economical molds - Mu, Yongcheng (Frontiers in Mechanical Engineering, 2024)
Introduction: As an economical and fast process method for surface modification of materials, overlay welding is increasingly widely used in the manufacturing and repair of parts in various industrial sectors. Methods: This study combines grating projection measurement to design an economical mold arc additive process, and introduces point cloud simplification algorithm for wear and repair design of the mold structure. Then, a new method for manufacturing low-cost, long-life, and economical hot stamping die inserts is designed, using low-cost forged steel and cast steel as substrates and surface welding of high-temperature alloy wear-resistant layers. Results and Discussion: The experiment shows that the proposed algorithm for simplifying scattered molds has a good evaluation effect, without any gaps, and has a good retention effect on point clouds. The maximum and minimum distances are 0.45 mm and 0.025 mm, respectively. The friction coefficient of cobalt based alloys at 300°C is lower than that at 200°C, and the fluctuation period at 200°C is significantly longer than that at 300°C. HSTS steel has the highest wear resistance, and the performance of cobalt-based alloys is significantly better than that of other alloys. The compressive yield strength of iron-based alloys is the highest, and the hardness of iron-based alloys is the highest, at 53.2 HRC. Therefore, iron-based alloys were selected as a surface wear-resistant layer welding material for economical molds with cooling channels, and cobalt-based alloys were also selected as a surface wear-resistant layer welding material for variable strength economical molds. The research results provide a reference for economic mold manufacturing and repair.